2019
DOI: 10.1002/hbm.24597
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating semantic and phonological contributions of the left inferior frontal gyrus to language production

Abstract: While the involvement of the left inferior frontal gyrus (IFG) in language production is undisputed, the role of specific subregions at different representational levels remains unclear. Some studies suggest a division of anterior and posterior regions for semantic and phonological processing, respectively. Crucially, evidence thus far only comes from correlative neuroimaging studies, but the functional relevance of the involvement of these subregions during a given task remains elusive. We applied repetitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 67 publications
2
57
0
Order By: Relevance
“…Vertex (Cz) was used as the control site because this area is a valid control condition, not associated with language processing [ 42 44 ]. The location of the vertex was determined manually as the midpoint between the lines connecting nasion and inion and tragi of the left and right ear in each subject as described previously [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vertex (Cz) was used as the control site because this area is a valid control condition, not associated with language processing [ 42 44 ]. The location of the vertex was determined manually as the midpoint between the lines connecting nasion and inion and tragi of the left and right ear in each subject as described previously [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…We used short bursts of 5 pulses as in our previous work in the language system [e.g. 25 , 45 ] to assure sufficient power of the stimulation effect. Such high-frequency online rTMS bursts typically affect cortical activity in the stimulated area for a period outlasting the stimulation for about half the duration of the stimulation train [ 52 ], and thus provide a temporal resolution in the range of hundreds of milliseconds [ 53 , 54 ], which would correspond to about 750 ms in our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically addressing the semantic-lexical interface relevant to word finding in thalamic aphasia, the left inferior frontal gyrus (LIFG) has long been considered critical for language production. Some evidence indicates anterior to posterior processing gradient, with the anterior LIFG more involved in processing the semantic properties and the posterior LIFG in processing the phonological properties of words (Devlin, Matthews, & Rushworth, 2003;Klaus & Hartwigsen, 2019), which is consistent with our observation that generating category members shows a large volume of activity around the left inferior frontal sulcus (the superior boundary of pars triangularis, i.e., anterior LIFG) and generating rhyming words shows a large volume of activity around the left precentral sulcus, (the posterior boundary of left pars opercularis, i.e., posterior LIFG) (Crosson et al, 2003). Finally, it should be noted that the information which anterior LIFG receives as a part of its semantic role in word retrieval is already highly differentiated semantically (e.g., see Lambon Ralph, Jefferies, Patterson, & Rogers, 2017 for one viewpoint).…”
Section: Applying the Cortical/thalamic Recurrent Circuit Model To Womentioning
confidence: 99%
“…Consequently, one may assume that when TMS is applied to a region that is expected to be involved in a given task before the cognitive process is executed, the initial neuronal activation state of that region is altered (i.e., suppressed), causing divergent behavioral effects (Stoeckel et al, 2009;Sandrini et al, 2011). In line with this argumentation, a previous study that also employed a 10 Hz TMS protocol during language production reported facilitation of phonological response speed in a rhyme generation task when TMS was given early after stimulus onset (Klaus and Hartwigsen, 2019). In that study, it was argued that TMS might have rather increased the amount of activity in the targeted pIFG to a level that was optimal for task performance, potentially resulting in a "preactivation" of phonological activity (see Töpper et al, 1998;Sparing et al, 2001, for a similar reasoning).…”
Section: Discussionmentioning
confidence: 83%